Moderate upswing in Euroland - Klaus-Jürgen Gern; Christophe Kamps; Carsten-Patrick Meier; Joachim Scheide (Institut für Weltwirtschaft (IfW), 2004)
Economic activity in the euro area is recovering. In the second half of 2003, real GDP grew at an annualized rate of roughly 1 percent. In contrast with other large industrialized countries, economy-wide capacity utilization has not yet increased. Private consumption has remained the major weak point. However, private investment has increased for the first time since 2 years and exports have risen rapidly, stimulated by the strong upswing in the rest of the world. A number of leading indicators suggest that the recovery in Euroland has gained some momentum since the turn of the year. Despite an expansionary monetary policy and the dynamic world economy, real GDP in the euro area will rise only moderately in comparison with earlier upswings. This is due to two factors. First, potential output growth in the euro area has apparently decelerated. Second, fiscal policy especially in the large euro-area economies is not sustainable. As governments do not have a credible consolidation strategy, the tax burden is likely to increase in the coming years. Against this background private households? income prospects are subdued and, as a consequence, private consumption will remain comparatively weak. The appreciation of the euro has had a considerable effect on economic activity, but it will not stop recovery. The results of our macroeconometric model imply also that the effects will be small in 2005 if, as we assume, the euro/ dollar exchange rate remains unchanged. Some observers urge the ECB to react to the strength of the euro by cutting interest rates. Whether the ECB should do so depends solely on the way in which the appreciation of the euro impacts the targets embedded in its monetary policy strategy. The main issue is whether the appreciation of the euro will push the inflation rate considerably below the target value. Past experience suggests that it would be unwise to assume it will have a strong dampening effect on consumer prices. Since the beginning of monetary union inflation forecasts have usually been too optimistic. All in all, the ECB is well advised not to cut interest rates in response to recent exchange rate developments. Interest rates in the euro area are already unusually low and stimulate economic activity. The Stability and Growth Pact requires the governments in euro-area countries to achieve a balanced budget or a budget surplus in the medium run. The main problem at present is not that budget deficit to GDP ratios are higher than 3 percent in some countries, but that structural deficits are also very high. Seven years after the adoption of the Pact the large countries still have made no progress on the way to a balanced budget. In Germany and France the structural deficits are even higher than before the monetary union. The recent Stability Programs of these countries suggest that the balanced- budget target has been given up altogether. This is eroding the credibility of fiscal policy and constitutes a heavy blow to economic stability in the euro area. Unsound fiscal policy negatively affects expectations in the private sector and is likely to result in a further deceleration of potential output growth.
Keywords: 330; Konjunktur; Europäische Wirtschafts- und Währungsunion; Konjunkturprognose; EU-Staaten